2020
DOI: 10.1167/tvst.9.5.9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Choroidal Neovascularization Perfusion: A Pilot Study With Laser Speckle Flowgraphy

Abstract: The purpose of this study was to quantify perfusion in the area of choroidal neovascularization (CNV) using laser speckle flowgraphy (LSFG) before and after intravitreal anti-vascular endothelial growth factor (VEGF) injection. Methods: Retrospective case series. Fifteen eyes of 15 patients with treatment-naïve CNV due to age-related macular degeneration (AMD) and with available LSFG images were included. The main outcome was the mean blur rate (MBR) quantified as a measure of perfusion within the CNV area obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
6
0
3
Order By: Relevance
“…The devices are equipped with an eyetracking system and with targets for internal and external fixation, so as to improve the acquisition in eyes with poor fixation. The technique showed high reproducibility in previous clinical studies (Aizawa et al 2011;Shiga et al 2014;Luft et al 2016;Calzetti et al 2018;Calzetti et al 2020b). All participants were asked to abstain from coffee, tea and alcohol intake within six hours of LSFG examination, as these substances are known to potentially affect MBR (Okuno et al 2000).…”
Section: Laser Speckle Flowgraphymentioning
confidence: 71%
See 1 more Smart Citation
“…The devices are equipped with an eyetracking system and with targets for internal and external fixation, so as to improve the acquisition in eyes with poor fixation. The technique showed high reproducibility in previous clinical studies (Aizawa et al 2011;Shiga et al 2014;Luft et al 2016;Calzetti et al 2018;Calzetti et al 2020b). All participants were asked to abstain from coffee, tea and alcohol intake within six hours of LSFG examination, as these substances are known to potentially affect MBR (Okuno et al 2000).…”
Section: Laser Speckle Flowgraphymentioning
confidence: 71%
“…2018; Calzetti et al. 2020b). All participants were asked to abstain from coffee, tea and alcohol intake within six hours of LSFG examination, as these substances are known to potentially affect MBR (Okuno et al.…”
Section: Methodsmentioning
confidence: 99%
“…One limitation of our study is that the anti-VEGF agents frequently given after 125 I-plaque brachytherapy [ 32 34 ] decrease retinal blood flow. In fact, several recent studies have deployed LSFG and reported reduced retinal perfusion, but which resolved by 2 months after injection [ 29 , 35 , 36 ]. Of note, in our cohort, only 1 patient was treated with bevacizumab less than 2 months before imaging.…”
Section: Discussionmentioning
confidence: 99%
“…This could be useful to determine whether the changes seen are related to the therapy or to random measurement errors. Third, we did not evaluate the correlations with visual function or other relevant biomarkers, such as those provided by OCT-A, and did not measure MBR of the neovascular area, which was proposed as a potential biomarker of MNV perfusion 37 . Lastly, it is known that intravitreal injections have a direct effect on intraocular pressure (IOP), which could interfere with retinal or choroidal blood flow.…”
Section: Discussionmentioning
confidence: 99%